Magnetic force microscopy of YLaFeO films implanted by high dose of nitrogen ions - Fodchuk, I.M.; Gutsuliak, I.I.; Zaplitniy, R.A.; Balovsyak, S.V.; Yaremiy, I.P.; Bonchyk, O.Yu.; Savitskiy, G.V.; Syvorotka, I.M.; Lytvyn, P.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The scattering field gradient maps of surface layer magnetic domains in Y₂.₉₅La₀.₀₅Fe₅O₁₂ iron-yttrium garnet modified by high-dose ion implantation with nitrogen ions N+ were obtained by the method of magnetic force microscopy. It was found that improving the magnetic properties of thin films, which includes reducing the observed magnetic losses after high-dose implantation, is accompanied by essential ordering of magnetic domains on the surface of the implanted films. There is a direct dependence of the magnetic properties on the dose of implanted atoms, accompanied by a significant dispersion and amorphization of surface layer and formation of a clear magnetic structure.